Feasibility and acceptability of cognitive behavioural therapy in older Japanese people with cognitive decline: a single-arm intervention. (1st December 2022) - Kashimura, Masami; Ishiwata, Akiko; Tateno, Amane; Spector, Aimee
Abstract: Studies have shown that cognitive behavioural therapy (CBT) for older people with cognitive decline and depression/anxiety improves negative moods. However, CBT research focusing on this population in Japan is limited. This study aimed to evaluate the feasibility of a cognitive behavioural program for people with cognitive decline. Sixteen Japanese patients with mild dementia ( n = 3) and mild cognitive impairment (MCI, n = 13) participated in the study. A single-arm, pre–post study was implemented in two hospitals in Japan. The CBT program included eight bi-weekly sessions. The feasibility outcomes (satisfaction, understanding and usefulness) were measured immediately after completing the sessions, and depression, anxiety, quality of life (QOL), neuropsychiatric symptoms, and caregiver burden were measured at three time points (i.e. before, immediately after, and 3-month follow-up). Ten MCI participants attended all sessions and the mean patient satisfaction scores using the Client Satisfaction Questionnaire were 31.0±10.05 out of 32. Linear mixed model analyses demonstrated that the time effect was significant for depression ( d = 1.62), anxiety ( d = 1.39), and QOL ( d = 1.00) for the patients, and significant for anxiety ( d = 1.08) for their caregivers. The study found that this CBT program is feasible and acceptable for older Japanese people with cognitive decline. The program also improved patients' QOL, anxiety and depressive symptoms, and decreased caregivers' anxiety. Key learning aims: (1) Recently, studies have shown that CBT for older people living with dementia has been effective in treating their depression and anxiety. However, evidence for the efficacy of CBT and other curative or care options for people living with dementia is limited in Japan. (2) We studied a short-period CBT program and found that it was likely to be feasible and acceptable for use among older Japanese people with mild cognitive impairment, that it may improve negative mood among this group, and that it may lessen the care burden for caregivers. (3) Furthermore, we found that caregiver involvement in the implementation of CBT for older people may be effective in improving the mood of family members.